Pharmaceutical Supply Chains - Medicines Shortages - Barbosa-Povoa, Ana Paula; Jenzer, Helena; de Miranda, João Luís (Lecture Notes in Logistics,, 2019)
This book provides an insight of relevant case studies and updated practices in "Pharmaceutical Supply Chains" (PharmSC) while addressing the most relevant topics within the COST Action "Medicines Shortages" (CA15105). The volume focuses on the most recent developments in the design, planning and scheduling of PharmSC, broadening from the suppliers' selection to the impact on patients and healthcare systems, addressing uncertainty and risk mitigation, and computational issues. It is directed at MSc/PhD students and young researchers (Post-Docs) in Pharmaceutics/Pharmaceutical sciences, Engineering fields, Economics/Management, as well as pharmaceutical decision makers, managers, and practitioners, and advanced readers demanding a fresh approach to decision making for PharmSC. The contributed chapters are associated with the homonymous COST Training Schools (TS), and the book creates a better understanding of the Action "Medicines Shortages" challenges and opportunities.